2015
DOI: 10.5811/westjem.2015.7.27185
|View full text |Cite
|
Sign up to set email alerts
|

Uterine Incarceration: Rare Cause of Urinary Retention in Healthy Pregnant Patients

Abstract: Gravid uterine incarceration (GUI) is a condition that is well discussed in literature; however, there are few acute diagnoses in the emergency department (ED). We present a case series where three multiparous females presented to the ED with non-specific urinary symptoms. On bedside ultrasound, each patient was noted to have a retroverted uterus and inferior bladder entrapment under the sacral promontory. GUI is a rare condition that can lead to uremia, sepsis, peritonitis, and ultimately maternal death. Emer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Bladder decompression techniques include hand reduction or implantation of an indwelling Foley catheter. A tenaculum should be applied to the cervix's posterior lip when the patient is in Trendelenburg or the kneechest position, according to another study [14]. After 20 weeks of pregnancy, a manual reduction is not advised since it increases the chance of preterm labor.…”
Section: Discussionmentioning
confidence: 99%
“…Bladder decompression techniques include hand reduction or implantation of an indwelling Foley catheter. A tenaculum should be applied to the cervix's posterior lip when the patient is in Trendelenburg or the kneechest position, according to another study [14]. After 20 weeks of pregnancy, a manual reduction is not advised since it increases the chance of preterm labor.…”
Section: Discussionmentioning
confidence: 99%
“…Han et al mention that, after the year 2000, the ability to diagnose IGU was superior and benefited from pelvic examination combined with imaging methods 1. Although there is no recognised standard test for IGU, both ultrasound and MRI seem to be adequate modalities 6 7 12 13…”
Section: Discussionmentioning
confidence: 99%
“…Occasionally, a soft pessary can be used[ 21 , 22 ]. Slama et al [ 23 ] used pessaries to alleviate successfully symptoms in 3 cases of urinary retention caused by uterine incarceration[ 23 ]. Yohannes et al [ 24 ] indicated that pessaries should not be used for impacted uterus as they are uncomfortable and cumbersome and restrict blood flow to the uterus[ 24 ].…”
Section: Discussionmentioning
confidence: 99%